Effect of temperature on infection and development of powdery mildew on cucumber. (21st May 2019) - Trecate, L.; Sedláková, B.; Mieslerová, B.; Manstretta, V.; Rossi, V.; Lebeda, A.
Abstract : Podosphaera xanthii and Golovinomyces orontii are the causal agents of cucurbit powdery mildew. The effect of temperature on conidial germination, infection and sporulation was studied under controlled conditions. Conidia were inoculated on cucumber leaf discs, and incubated at six constant temperatures (from 10 to 35 °C in 5 °C steps) for 3 to 72 h to evaluate conidial germination and infection, and for 6–15 days to evaluate sporulation intensity. Germination took place at all tested temperatures, but was close to zero at 35 °C. The longest germ tubes measured in this experiment were 141.74 μm for the secondary germ tube of P . xanthii at 20 °C after 48 h of incubation, and 67.92 μm for G. orontii for the primary germ tube at 20 °C after 48 h of incubation. The optimal temperatures for conidial germination, infection and sporulation were 24.4, 25.7 and 22.3 °C, respectively, for P. xanthii, and 17.9, 17.3 and 14.9 °C, respectively, for G. orontii . Equations were developed to describe conidial germination with a coefficient of determination ( R 2 ) of 0.85 and 0.90 for P. xanthii and G . orontii, respectively. Infection equations resulted in R 2 of 0.94 and 0.93 for P . xanthii and G . orontii, respectively; and for sporulation, R 2 of 0.75 and 0.76 for P. xanthii and G. orontii respectively, as a function of temperature. These results can be used to develop models for the risk of cucurbit powdery mildew under field conditions.